A Formal Model for Partitioning based Aspect Mining - Cojocar, Grigoreta Sofia (Moldovan); Serban, Gabriela (INFOCOMP Journal of Computer Science, 2007)
Separation of concerns is a very important principle of software engineering that, in its most general form, refers to the ability to identify, encapsulate and manipulate those parts of a software system that are relevant to a particular concept, goal, or purpose. Aspect Oriented Programming provides means to encapsulate concerns which cannot be modularized using traditional programming techniques. These concerns are called crosscutting concerns. Aspect Mining is a research direction that tries to identify crosscutting concerns in legacy systems. The aim of this paper is to introduce a new formal model for partitioning based aspect mining. Such a model was not defined in the literature, yet. The applicability of the proposed formal model is studied on three different aspect mining techniques.